When helping hurts: validating a measure of compulsive helping and exploring potential correlates - Workman, Katey; Padilla-Walker, Laura M.; Reschke, Peter J.; Rogers, Adam A. (Frontiers in Psychology, 2025)
IntroductionThis cross-sectional study proposes and validates a new measure of compulsive helping: helping which harms the helper.MethodsEmerging Adults (N = 438; Mage = 20.29, SD = 1.04, 51.71% Female) reported on compulsive helping. Confirmatory factor analysis was used to assess construct validity, while bivariate correlations were used to assess convergent and discriminant validity.ResultsConfirmatory factor analysis suggested convergent validity with all 10 items loading onto a single factor, with factor loadings above 0.44. Model fit was acceptable. Convergent validity was demonstrated such that compulsive helping was positively correlated with prosocial behavior and anxiety. Discriminant validity was demonstrated such that compulsive helping was negatively associated with self-regulation.ConclusionThis new concept and measure of compulsive helping is a first step toward defining the limits of the adaptiveness of prosocial behavior. Though not frequent, it appears helping which is harmful is not uncommon. Future research should employ qualitative means and consider the multidimensionality of prosocial behavior.